Perlindungan Terhadap Kepentingan Kreditor Melalui Actio Pauliana - Siti Anisah (Jurnal Hukum IUS QUIA IUSTUM, 2009)
Generally, the procedure to prove the application of actio pauliana is not simple. In addition to this, the application for the settlement of actio pauliana is lack or coordination among the relevant authorities. It is considered therefore that the protection on creditor’s interest through actio pauliana is possible to be enforced. More than this, further regulation on the implementation of the procedure to prove actio pauliana which is implementable is highly demanded.Keywords: Act Of Bankruptcy, Creditor, Actio Pauliana